‘We’re the First Port of Call’ – Perspectives of Ambulance Staff on Responding to Deaths by Suicide: A Qualitative Study - Nelson, Pauline A.; Cordingley, Lis; Kapur, Navneet; Chew-Graham, Carolyn A.; Shaw, Jenny; Smith, Shirley; McGale, Barry; McDonnell, Sharon (Frontiers in Psychology, 2020)
Introduction Exposure to suicide is a known risk factor for suicide. Ambulance staff are exposed to work-related stressors including attending suicides, which may elevate their risk for mental health problems/suicide. Little is known about ambulance staff’s perspectives on how they experience these events and whether they feel equipped to respond to bereaved families at the scene of death. This study explores the perspectives of ambulance staff about responding to deaths by suicide. Materials and methods A convenience sample of ambulance staff recruited from one ambulance service in England. In-depth, qualitative, semi-structured face-to-face interviews conducted with nine ambulance staff (six male, three female) to explore experiences of responding to suicide. Data analysed using thematic analysis. Results Participants reported the experience of job-related strain including exposure to the suicide/suicidal ideation of colleagues; they described suppressing their distress despite significant emotional impact. All participants had been personally bereaved by suicide and responding to suicide was a common part of their job. They were often the first professionals at the scene, and undertook varied and often conflicting roles: negotiating with patients in crisis; informing individuals of the death of a loved one; preserving the body/potential crime scene; dealing with the intense emotional reactions of bereaved individuals. Participants reported long-term, salient memories of these events; however there was a reported lack of acknowledgement in the workplace that suicides may be traumatic and no guidance for staff on how to cope. Opportunities to debrief were reportedly rare, and there was reluctance to access work-based liaison services. Training in how to respond to individuals bereaved by suicide was also lacking. Discussion The study is the first to reveal the complex challenges faced by ambulance staff in responding to suicide without adequate training and support. It demonstrates the potential impact that responding to suicide can have personally and professionally on staff, and emphasises the need for employers to support staff wellbeing in better ways. Training and postvention support could enable better coping among staff, more effective support for bereaved individuals and reduce the risk of death by suicide both in those bereaved by suicide and in ambulance staff.